Bianchi identities for an N=2, d=5 supersymmetric Yang-Mills theory on the group manifold - Borges, M. F. [UNESP] (Elsevier B.V., 1996)
The purpose of this note is the construction of a geometrical structure for a supersymmetric N = 2, d = 5 Yang-Mills theory on the group manifold. From a general hypothesis proposed for the curvatures of the theory, the Bianchi identities are solved, whose solution will be fundamental for the construction of the geometrical action for the N = 2, d = 5 supergravity and Yang-Mills coupled theory.
Keywords: Bianchi identities; Supergravity; Yang-Mills theory